KEBIASAAN MINUM, KONSUMSI CAIRAN DAN STATUS HIDRASI PADA ATLET SOFTBALL KONI BANTEN TAHUN 2016 - Kuswari, Mury (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
Achievements of Indonesian athlete are likely to experience ups and downs even lately tend to decline in the international championship such as SEA Games and ASIAN Games. The achievements of athletes are influenced by several factors one of those is related to nutrition namely water. Inadequate fluid consumption may affect fatigue, hydration status, and performance of athletes. The objective of this study is to analyze different between drinking habits, consumption of fluids, physical activity and level of hydration in athletes of softball in KONI Banten 2016. The study uses a quantitative research design with cross sectional study design. The population in this study were all athletes softball in KONI Banten. Analysis of the data in this study using Chi Square and One Way Anova. This technique is used to measure the drinking habits, consumption of fluids, and level of hydration athletes of softball in KONI Banten 2016. The results of statistical analysis Chi Square test between drinking habits and hydration significant, One Way Anova test between fluid consumptions and hydration significant. The statistical result showed a drinking habits, the consumption of fluids, and the allowance affect level of hydration. Keywords : Drinking Habits, Consumption of Fluids, Physical Activity, Hydration